Analyzing radiative heat on third-grade fluids over an expanding inclined sheet subject to higher-order chemical reaction: An overlapping grid spectral quasilinearization approach - Titilayo M Agbaje; Folarin Oluwaseun; S.R. Mishra; Rupa Baithalu; Subhajit Panda (Partial Differential Equations in Applied Mathematics)
Higher-order chemical reactions significantly enhance the concentration of the fluid indicating its vital role in processes involving radiative species. Therefore, the observation shows its important practical applications in industrial processes such as polymer extrusion, in which heat transfer properties are useful in the production of quality products. The proposed study emphases on the free convection of a third-grade fluid via an inclined expanding sheet for the influence of radiative heat and higher-order chemical reactions. However, the analysis incorporates the influence of viscous dissipation that is significant in determining the thermal behavior of the fluid. Further, the proposed flow phenomena governed by the set of partial differential equations are transformed into ordinary ones by the operating of suitable similarity rules. The transformed equations equipped with characterizing parameters are handled by a numerical technique known as the over lapping grid spectral quasilinearization method. The quantitative behavior of the factors intricate in it is deployed graphically and described briefly. However, the important outcomes of the study are; Richardson number is useful in enhancing the fluid momentum whereas the impact is reversed for the temperature and concentration distribution. Further, increasing heavier species i.e., Schmidt number attenuates the concentration profile.